A hybrid de-noising method for mammogram images - Rashid Mehmood Gondal; Saima Anwar Lashari; Murtaja Ali Saare; Sari Ali Sari (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In general, mammogram images contaminated with noise which directly affect images quality. Several methods have been proposed to de-noise these images, however, there is always a risk of losing valuable information. In order to overcome the loss of information, the present study proposed a hybrid denoising method for mammogram images. The proposed hybrid method works in two steps: Firstly, preprocessing with mathematical morphology was applied for image enhancement. Secondly, global unsymmetrical trimmed median filter (GUTM) is applied to de-noise image. Experimental results prove that proposed method work well for mammogram images. Hence, the study provided an alternative method for denoising mammogram images.